2016
DOI: 10.3168/jds.2015-9928
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationships among alternative definitions of feed efficiency in grazing lactating dairy cows

Abstract: International interest in feed efficiency, and in particular energy intake and residual energy intake (REI), is intensifying due to a greater global demand for animalderived protein and energy sources. Feed efficiency is a trait of economic importance, and yet is overlooked in national dairy cow breeding goals. This is due primarily to a lack of accurate data on commercial animals, but also a lack of clarity on the most appropriate definition of the feed intake and utilization complex. The objective of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
6
39
0
1
Order By: Relevance
“…Ratio traits that compare output (production) to input (intake) are common, but they do not adequately account for differences in cows for energy partitioning toward milk production, body maintenance, or mobilization of body tissue (Veerkamp and Emmans, 1995;Berry and Crowley, 2013). Many of the ratio measures of FE in the study by Hurley et al (2016) were not correlated, which suggested alternative measures of FE might describe different aspects of FE.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ratio traits that compare output (production) to input (intake) are common, but they do not adequately account for differences in cows for energy partitioning toward milk production, body maintenance, or mobilization of body tissue (Veerkamp and Emmans, 1995;Berry and Crowley, 2013). Many of the ratio measures of FE in the study by Hurley et al (2016) were not correlated, which suggested alternative measures of FE might describe different aspects of FE.…”
Section: Introductionmentioning
confidence: 96%
“…Universal agreement on the optimum measure of FE for dairy cattle has not been achieved (Coleman et al, 2010;Hurley et al, 2016), and this adds to the complexity of assessing FE. For example, Hurley et al (2016) reported relationships among 14 alternative definitions of energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a gradual multiple linear regression approach, only those variables were included which were suggested to represent so-called energy sinks explaining variance in the observed net energy lactation intake (NEL-in obs ) (Hurley et al 2016, Potts et al 2015, Xi et al 2015) and which were proven to contribute significantly to the regression. Therefore, energy corrected milk (ECM), days in milk (DIM), metabolic body weight (b.w.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter is frequently used as an efficiency trait and for investigating the unaccounted variance in NEL-intake in relation to other parameters (e.g. Hurley et al 2016, Potts et al 2015, Xi et al 2015). …”
Section: Sample Preparation and Analysesmentioning
confidence: 99%